2015
DOI: 10.1126/science.aab1601
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex single-cell profiling of chromatin accessibility by combinatorial cellular indexing

Abstract: Technical advances have enabled the collection of genome and transcriptome datasets with single-cell resolution. However, single-cell characterization of the epigenome has remained challenging. Furthermore, because cells must be physically separated prior to biochemical processing, conventional single-cell preparatory methods scale linearly. We applied combinatorial cellular indexing to measure chromatin accessibility in thousands of single cells per assay, circumventing the need for compartmentalization of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
1,119
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 1,144 publications
(1,128 citation statements)
references
References 39 publications
7
1,119
0
2
Order By: Relevance
“…This field has been propelled by remarkable technological advances for efficiently isolating single cells 28, 29, and the reduction of the detection levels of protocols for profiling gene expression 30, 31, histone marks 25, 26, or chromatin accessibility 32, 33 in individual cells. These techniques allow researchers to overcome the limitations of population studies, in which averaging the measurements over a heterogeneous population of cells masks the variability at the epigenetics and transcriptional levels among cells within a culture or tissue 26, 34, 35.…”
Section: Single‐cell Profiling Is Key For Studying Pluripotent Statementioning
confidence: 99%
See 2 more Smart Citations
“…This field has been propelled by remarkable technological advances for efficiently isolating single cells 28, 29, and the reduction of the detection levels of protocols for profiling gene expression 30, 31, histone marks 25, 26, or chromatin accessibility 32, 33 in individual cells. These techniques allow researchers to overcome the limitations of population studies, in which averaging the measurements over a heterogeneous population of cells masks the variability at the epigenetics and transcriptional levels among cells within a culture or tissue 26, 34, 35.…”
Section: Single‐cell Profiling Is Key For Studying Pluripotent Statementioning
confidence: 99%
“…In contrast to previous computational methods for analyzing single cell data for identifying lineage specifiers 80, 81, 82, which rely on the identification of trends in the expression of individual genes in different subpopulations, in this study we have demonstrated that information of the interactions among genes in the subpopulation‐specific GRNs, is key for predicting the genes triggering differentiation reported experimentally 74. These network models 73, 74, 102, 103 relying solely on transcriptomics data could be significantly improved by overlaying epigenetics data 25, 32, 33, for contextualizing regulatory interactions at the transcriptional level depending on the chromatin state – e.g. open/close chromatin regions, and activating/inhibitory chromatin marks patterns 25, 26, 32, 33.…”
Section: Modeling Heterogeneity In the Pluripotent State Will Be Essementioning
confidence: 99%
See 1 more Smart Citation
“…The set of 96 wells are then pooled and then 15-25 of these randomly indexed nuclei are deposited by a second round of FANS into each well of one or more new 96-well plates. The probability of any two nuclei within the new well being derived from the same origin well is low (6-11%) 16 . Each new well is then uniquely indexed by PCR followed by pooling all individual reactions, purification, and sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…The combinatorial indexing concept, which involves two tiers of library indexing (transposase stage and PCR stage) was integrated with the widely utilized assay for transposase accessible chromatin (ATAC-seq) 15 , to simultaneously produce profiles of active regulatory elements in thousands of single cells 16 (scATAC-seq, Fig. 1a).…”
Section: Introductionmentioning
confidence: 99%